Numerical simulation of pyramid solar stills with finned absorbers: Enhancing thermal efficiency for sustainable desalination - Angham Fadil Abed; Mohammed J. Alshukri; Rassol Hamed Rasheed; Luay S. Al-Ansari; Ahmed Mohsin Alsayah; Mahmoud Khaled (Case Studies in Thermal Engineering)
Solar desalination provides a sustainable method of producing freshwater in desert areas with limited access to electricity and drinkable water. Improving solar still efficiency is essential to increasing the viability and efficacy of this technology. The objective of this study is to determine the effect of adding square, pyramid and cylindrical-shaped fins on a pyramid solar still's efficiency and to parametrically analyze the thermal performance of the device. Although other studies have looked at a variety of designs to optimize the performance of solar stills, this study is unusual in that it compares fins with square, pyramid and cylinerical shapes, offering fresh perspectives on the best design arrangements for increased thermal efficiency. Four configurations—a flat plate conventional pyramid solar still (FPCPS), a square finned plate pyramid solar still (SFPPS), pyramid finned plate solar still (PFPPS), and a cylindrical finned plate pyramid solar still (CFPPS) —were simulated using COMSOL Multiphysics 5.4. To evaluate their impact on thermal performance, important parameters such fin height, thickness, number of fins, and water depth were systematically changed. The simulations showed that while increasing fin thickness and quantity has a negative effect on performance, increasing fin height improves efficiency for square, pyramid-shaped and cylindrical fins. With ideal fin numbers (Nf = 25) and lengths (Lf = 0.04 m) and a basin projected area of 1 m2, the SFPPS and CFPPS configurations specifically obtained an efficiency boost of 112.2 % and 102.8 %, while the PFPPS demonstrated a 79.2 % enhancement in comparison to the traditional design. For the FBCPS, SFBPS, PFBPS, and CFPPS, the highest measured thermal efficiencies were 38.11 %, 56.15 %, 54.20 %, and 55.40 %, respectively. These results highlight how important fin geometry is for maximizing pyramid solar stills' thermal performance.